Strategi Peningkatan Efisiensi dan Daya Saing Pemasaran Cengkeh untuk Meningkatkan Kesejahteraan Petani: Pendekatan Sosial Ekonomi dan Manajerial - Kadir, Abdul; Sampara, Nirwana; Halimah, Andi Sitti (Universitas Galuh, 2025)
This study aims to analyze the efficiency and competitiveness of clove marketing and to formulate improvement strategies to support farmers’ welfare. The approach used is socio-economic and managerial, employing survey methods and quantitative analysis. The results indicate that the clove marketing system is relatively efficient, with a farmer’s share of 78.8%, but farmers still hold weak bargaining positions. Multiple linear regression tests show that capital, labor, and production have significant effects on farmers’ income. The recommended priority strategy based on SWOT and QSPM analysis is the strengthening of marketing cooperatives. An integrative approach is needed to sustainably enhance competitiveness and farmers’ welfare.